Antiperiodic Boundary Value Problems for Impulsive Fractional Functional Differential Equations via Conformable Derivative. (31st December 2018) - Wang, Jingfeng; Bai, Chuanzhi
Abstract : In this paper, by using the lower and upper solution method and the monotone iterative technique, we investigate the existence of solutions to antiperiodic boundary value problems for impulsive fractional functional equations via a recent novel concept of conformable fractional derivative. An example is given to illustrate our theoretical results.